The Non-structural Protein 5 and Matrix Protein Are Antigenic Targets of T Cell Immunity to Genotype 1 Porcine Reproductive and Respiratory Syndrome Viruses - Mokhtar, Helen; Pedrera, Miriam; Frossard, Jean-Pierre; Biffar, Lucia; Hammer, Sabine E.; Kvisgaard, Lise K.; Larsen, Lars E.; Stewart, Graham R.; Somavarapu, Satyanarayana; Steinbach, Falko; Graham, Simon P. (Frontiers in Immunology, 2016)
The porcine reproductive and respiratory syndrome virus (PRRSV) is the cause of one of the most economically important diseases affecting swine worldwide. Efforts to develop a next-generation vaccine have largely focussed on envelope glycoproteins to target virus-neutralising antibody responses. However, these approaches have failed to demonstrate the necessary efficacy to progress towards market. T cells are crucial to the control of many viruses through cytolysis and cytokine secretion. Since control of PRRSV infection is not dependent on the development of neutralising antibodies, it has been proposed that T cell mediated immunity plays a key role. We therefore hypothesised that conserved T cell antigens represent prime candidates for the development a novel PRRS vaccine. Antigens were identified by screening a proteome-wide synthetic peptide library with T cells from cohorts of pigs rendered immune by experimental infections with a closely-related (subtype 1) or divergent (subtype 3) PRRSV-1 strain. Dominant T cell IFN-γ responses were directed against the non-structural protein 5 (NSP5), and to a lesser extent, the matrix (M) protein. The majority of NSP5-specific CD8 T cells and M-specific CD4 T cells expressed a putative effector memory phenotype and were polyfunctional as assessed by co-expression of TNF-α and mobilisation of the cytotoxic degranulation marker CD107a. Both antigens were generally well conserved amongst strains of both PRRSV genotypes. Thus M and NSP5 represent attractive vaccine candidate T cell antigens which should be evaluated further in the context of PRRSV vaccine development.